2015
DOI: 10.4172/2167-0943.1000186
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Metabolic Syndrome among Mbo Women Yaounde -Cameroon

Abstract: Objective: This study aimed to evaluate the metabolic syndrome among Mbo ethnic group women living in Yaounde, Cameroon. Methods: The study was conducted on ninety-two women aged between 18-60 years who were referred to the Andre Fouda Medical Fundation in Yaounde. Metabolic syndrome was diagnosed using Adult Treatment Panel-III (ATP-III) 2001 guidelines. Results: The mean of age, high fasting blood glucose, triglycerides levels and total cholesterol levels were significantly (p<0.05) higher in women with meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 18 publications
1
2
1
Order By: Relevance
“…This metabolic syndrome prevalence is high than that reported among previous metabolic syndrome women studies in Cameroon. [22,23,24,25] The cholesterol in our study is in accordance with previous studies, Turkish [26] , Canadian [27] , Bamiléké [22] studies also shows that low HDL cholesterol is the most common found risk factor in women having metabolic syndrome.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This metabolic syndrome prevalence is high than that reported among previous metabolic syndrome women studies in Cameroon. [22,23,24,25] The cholesterol in our study is in accordance with previous studies, Turkish [26] , Canadian [27] , Bamiléké [22] studies also shows that low HDL cholesterol is the most common found risk factor in women having metabolic syndrome.…”
Section: Discussionsupporting
confidence: 91%
“…[28] The frequency of metabolic syndrome was highest in the study, although the genetic aspects of metabolic syndrome is quite important, several studies have revealed that lifestyle change also play a important role, in general. The list of factors that could justified the metabolic syndrome prevalence are, ignorance, unhealthy attitudes, low physical activity [29,30] , environmental factors, such as working hours, sociocultural factors, as nibbling, food overconsumption, physiological changes. [31] Physical inactivity is well recognized among Cameroon [29] women and worldwide [30] to be a contributing factor for chronic diseases…”
Section: Discussionmentioning
confidence: 99%
“…This prevalence is was considerably higher than previous reports on Sokoto civils servants women in Nigeria [26] , also to other Cameroonians studies [21,22] and lower to bamileke women study. [20] The comparison of our findings with another studies are limited because of the few available data of metabolic syndrome prevalence from civil servants populations in Africa as.…”
Section: World Journal Of Pharmacy and Pharmaceutical Sciencescontrasting
confidence: 69%
“…[18,19] They are already several metabolic syndrome studies in Cameroon. [20,21,22] and it's prevalence in previous studies as ranged between 0.2%. [23] and 60.4%,.…”
Section: Discussionmentioning
confidence: 97%